Giemsa-stained thick blood films as a source of DNA for Plasmodium species-specific real-time PCR - Cnops, Lieselotte (BioMed Central, 2010)
BACKGROUND: This study describes the use of thick blood films (TBF) as specimens for DNA amplification with the Plasmodium species-specific real-time PCR that was recently validated on whole blood samples. METHODS: The panel of 135 Giemsa-stained clinical TBFs represented single infections of the four Plasmodium species with varying parasite densities or only gametocytes, mixed infections, and negative samples and was stored for up to 12 years. Half of the Giemsa-stained TBF was scraped off by a sterile scalpel and collected into phosphate buffered saline. DNA was extracted with the Qiagen DNA mini kit with minor modifications. DNA was amplified with the 18S rRNA real-time PCR targeting the four Plasmodium species with four species-specific primers and probes in combination with one genus-specific reverse primer. Results of the PCR on TBF were compared to those of the PCR on whole blood and to microscopy. RESULTS: Correct identification for single species infections was obtained for all TBF samples with Plasmodium falciparum (n = 50), Plasmodium vivax (n = 25), Plasmodium ovale (n = 25) and in all but one samples with Plasmodium malariae (n = 10). Compared to whole blood samples, higher Ct-values were observed by PCR on TBF with a mean difference of 5.93. Four out of five mixed infections were correctly identified with PCR on TBF. None of the negative samples (n = 20) gave a PCR signal. PCR on TBF showed a detection limit of 0.2 asexual parasites/μl compared to 0.02/μl for whole blood. Intra-run variation was higher for PCR on TBF (%CV 1.90) compared to PCR on whole blood (%CV 0.54). Compared to microscopy, PCR on TBF generated three more species identifications in samples containing a single species and detected the same four mixed-infections. CONCLUSIONS: Giemsa-stained TBFs are a reliable source of DNA for Plasmodium real-time PCR analysis, allowing applications in reference and research settings in case whole blood samples are not available.